2018
DOI: 10.1016/j.ijnurstu.2018.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the workplace on physical activity and cardiometabolic health: Results of the multi-centre cross-sectional Champlain Nurses’ study

Abstract: Nurses are not meeting current physical activity guidelines (150 min of moderate-to-vigorous intensity physical activity per week in 10-min bouts), yet exceeded these recommendations when examining their continuous (i.e. non bouts) physical activity levels. No association between the PWE and moderate-to-vigorous intensity physical activity was observed. Rotating vs. fixed shifts, 12- vs. 8-h shifts, and/or full-time or part-time vs. casual hours may impede nurses' ability to meet recommended physical activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
1
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 60 publications
1
66
1
1
Order By: Relevance
“…Only 23% of nurses had adequate/higher levels of MVPA, which is likely why we observed the strongest positive association with mood state. A closer look at this sample revealed that mental health conditions such as depression (9.1%) and anxiety (7.0%) were prevalent (Reed et al, 2018). Findings from this study revealed that nurses' MVPA levels were significantly related to measures of mood states, which can potentially affect their mental health.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…Only 23% of nurses had adequate/higher levels of MVPA, which is likely why we observed the strongest positive association with mood state. A closer look at this sample revealed that mental health conditions such as depression (9.1%) and anxiety (7.0%) were prevalent (Reed et al, 2018). Findings from this study revealed that nurses' MVPA levels were significantly related to measures of mood states, which can potentially affect their mental health.…”
Section: Discussionmentioning
confidence: 75%
“…This is a secondary analysis of data from the cross-sectional Champlain Nurses' Study. Details about the study have been published elsewhere (Reed et al, 2018…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The "physical activity paradox" suggests that PA undertaken at work differs in quality, quantity and health effects than PA performed during leisure-time [13]. For example, occupational PA carried out at lower intensities may not elicit substantial improvements in cardiorespiratory fitness, such as in the case of nurses who have been shown to spend a large proportion of their wakeful time in light intensity PA (LPA) [14]. Recent systematic review evidence also suggests that higher levels of occupational PA (even while controlling for leisure-time MVPA) are associated with an increased risk in premature mortality in men [15].…”
Section: Introductionmentioning
confidence: 99%